Differences between male and female elite free-style wrestlers in the effects of "set up" on leg attack - Ito, S.; Crawshaw, L.; Kanosue, K. (Archives of Budo, 2019)
Background and Study Aim: Leg attack is the most basic skill in free-style wrestling. Before executing a leg attack, balance and anticipation of the opponent must be disrupted. We defined this action as the "set up". The aim of this study is knowledge about the effects of "set up" on the success rate of leg attacks, and answer to question: whether or not a gender difference exists in the use and effectiveness of "set ups" in the elite level of the wrestling matches.